The Enigmatic Upper Ordovician of the Naturtejo UNESCO Global Geopark (Portugal) - Sofia Pereira; Jorge Colmenar; Cristiana Esteves; Ícaro Dias da Silva; Miguel Pires; Carlos Neto de Carvalho (Geoconservation Research)
Naturtejo UNESCO Global Geopark (Portugal) area includes deposits from the Neoproterozoic to the Quaternary. Despite its limited exposure area in major Variscan folded structures, the Ordovician series hosts some of its most famous geological heritage features, such as the Penha Garcia Ichnological Park.  The Upper Ordovician of the Central Iberian Zone is still far from being as well-understood as it is in other areas. Extensional tectonics, magmatism, global eustatic and climatic changes generated a great variability of sequences in a reduced geographical area. The Upper Ordovician of the Naturtejo region, often considered poorly represented, is here demonstrated to have a great potential and to be more complete than previously assumed. New stratigraphic and paleontologic data are presented for the three Upper Ordovician-bearing structures within Naturtejo: Fajão-Muradal, Vila Velha de Ródão and Penha Garcia synclines. Remobilized upper Katian fossiliferous clasts were found for the first time within the Hirnantian Casal Carvalhal from the Fajão-Muradal Syncline and a new fossil site is added to the Orvalho GeoTrail. In the Vila Velha de Ródão Syncline, the Barroca da Senhora stream fossil site constitutes a new geosite within the protected area of Portas de Ródão Natural Monument, presenting the most complete Upper Ordovician sequence of this structure. Finally, the stratigraphic and paleontologic record of the Vale Feitoso estate offers all the conditions to propose a new theme geotrail, diversifying the tourism in the Monfortinho village (Penha Garcia Syncline).